EARLY WARNING SYSTEM UNTUK MONITORING KINERJA DOSEN - . Riyanto; Harco Leslie Hendrik S.W. (Universitas Insan Pembangunan Indonesia, 2016)
Abstract— Monitoring the performance of lecturers is veryimportant for the division portion faculty workload accordingto Tridharma Pendidikan. Lecturer Workload should bein monitoring anytime and anywhere that can be conducted inaccordance with the portion of the standards prescribed. Thisstudy aims to divide the portion of faculty workload inaccordance with the standards prescribed and monitor theperformance of lecturers in accordance TridharmaPendidikan. With the methods to be used in analyzing anddesigning systems is Object Oriented Analysis andDesign using the Unified Modeling Language. The resultsof the research in the form of application development is EarlyWarning System which can be accessed via the web to monitorthe performance of lecturers, and will provide a referencefor executing a lecturer who does not conform with thestandards that have been granted by the Government ofIndonesia.Keywords— Early Warning System, Monitoring, LecturerWorkload (BKD), Performance, Lecturer